Two Decades of HELINA Conferences: A Historical Review of Health Informatics in Africa - Korpela, M. (Yearbook of Medical Informatics, 2013)
Objective: Review the history of health informatics in Africa as projected by the HELINA conferences, to draw inferences for the next phase.Methods and materials: Summarising from the proceedings of HELINA 93, unpublished programmes and reports of later conferences, abstracts and presentations on the web sites of the most recent conferences, and personal recollections of all but one of the conferences. Analysing the e-health situation in Africa in 1993, 2007 and 2011 by mapping software applications presented in the respective conferences on a simplified model of potential spots for e-health use.Results: The following phases were identified: Pre-phase from 1979; individual scientific papers. Phase 1, the 1993-1999 conferences; carried by the momentum of HELINA 93. Phase 2, interregnum; difficulty to find conference organisers. Phase 3, the 2007-2011 conferences; carried by the HELINA association as IMIA Africa Region. Currently most of the important spots for e-health use are being populated by appropriate software applications, mostly by collaborative open source projects. Phase 4 starting, characterised by the expansion of e-health practice on the continent, the HELINA association as a key organiser, and annual HELINA conferences becoming scientifically stronger and more visible.Conclusions: Key issues in making health informatics blossom in Africa include local development capacity, community orientation, collaborative design, international collaboration, government support, champions and organised continent-wide collaboration.
Keywords: Health informatics; Africa; history